Anatomical structure and antioxidant activity of red bulb plant - EVI MINTOWATI KUNTORINI; MARIA DEWI; MISRINA MISRINA (Society for Indonesian Biodiversity, 2016)
Kuntorini EM, Dewi M, Misrina. 2016. Anatomical structure and antioxidant activity of red bulb plant (Eleutherine americana) on different plant age. Biodiversitas 17: 229-233. Eleutherine americana Merr is an medicinal herb named â€œred bulbâ€ or â€œbawang dayakâ€. Red bulb plant is commonly used as anti-breast cancer in Kalimantan, which may be linked to their bioactive naphtoquinone-derivatives properties. The aim of this study was to characterize the anatomical structure and antioxidant activity in red bulb of different ages. The anatomical structure of bulb was fixed and prepared following paraffin embedding techniques. Measurement of antioxidant activity carried out using the DDPH method. The anatomical structure of red bulb showed that the P2 = 93 ppm, but weaker than vitamin C (IC 50 = 3.03 ppm) and BHT (IC50 = 5.52 ppm)Â as a control.